A Comprehensive Review of Olax scandens Roxb. (Dheniaani) - Zareen, Nazia; Venkatesh, Sama; Rao, V.V. Basava; Kiran, A. Ravi (Pharmacognosy Reviews)
Olax scandens Roxb. is a scandent, thorny shrub up to 5 metres tall widely distributed throughout Asia. It is traditionally used to treat diseases like anaemia, headache, diarrhoea, joint pains, intestinal and liver diseases, psoriasis, filaria and as a supporting drug to treat diabetes. The phytochemical screening of various parts reported presence of saponins, steroids, triterpenoids, phenolic compounds, alkaloids, flavonoids and carbohydrates. Pharmacologically it is reported to have antimicrobial, antipyretic, anti-inflammatory, antioxidant activity and to synthesise nanoparticles using O. scandens leaf extract for anticancer study. The present comprehensive review summarises the traditional claims, phytochemistry and pharmacological activities of O. scandens reported in scientific literature. The plant Olax scandens Roxb. has innumerable traditional uses and is also used in many folk remedies. Hence comprehensive review is necessary for this plant, to correlate its traditional uses with scientific literature available on it. Further scope of research on this plant lies in extensive and long-term studies on its pharmacological activities, identification of possible lead molecules, standardisation of different parts of the plant to prevent its adulteration.
Keywords: Olax scandens; Phytochemistry; Pharmacognosy; Pharmacology; Traditional uses